Efecto del acetato de plomo en el crecimiento de Lobularia maritima (L.) Desv. "lágrimas de virgen" (Brassicaceae) cultivada en condiciones de Invernadero - Alfaro Bardales, María Mercedes (2023)
Lead is one of the main heavy metals that can cause adverse effects on human health and plant growth. Various plant species are used in lead-contaminated environments, finding variations in their response capacity in relation to their growth and development. In the present investigation, the effect of 4 concentrations of lead acetate (0, 400, 600 and 800 ppm) on the growth of L. maritima Desv. at 30, 60 and 90 days of cultivate under greenhouse conditions. For this, plants grown in perlite substrate, irrigated with nutrient solution and lead acetate, following a completely randomized experimental design. Growth was evaluated based on: root and stem length, leaf area, and number of branches with inflorescence. Lead acetate was found to cause a decrease in the growth parameters analyzed; observing the lowest values at the concentration of 800 ppm in the first 2 periods of time.